On the uniqueness of elements of the best approximation and the best one-sided approximation in the space L_1 - Babenko, V. F.; Glushko, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
The problem of uniqueness of the best approximations in the space L_1[a, b] is studied We consider the problem of the best approximation and the best (α, β)-approximation of continuous functions and the problem of the best one-sided approximation of continuously differentiable functions.